Performance evaluation of new steel frame buildings for seismic behaviour. - Lee, Kihak (Earthquake engineering & structural dynamics.)
The damage observed after the Northridge Earthquake exposed a weakness of design and construction procedures and led to the development of performance based guidelines for design of new steel frame structures. As part of Phase 2 of the FEMA/SAC project, this study focused on performance prediction of new steel special moment resisting frame buildings assumed to be built after the Northridge earthquake. A total of 26 post Northridge buildings that represent typical steel SMRF buildings based on the new seismic code (1997 NEHRP) and pre-qualified post Northridge connections were designed. Then, the analytical building models considering the effects of ductile connections, panel zone deformation and interior gravity frames were developed and subjected to sets of 20 SAC ground motions representing the 2/50 and 50/50 hazard levels. A new procedure that allows the design professional to determine the confidence level for achieving a given performance objective is presented. Using the drift demand and capacities, confidence levels that post Northridge buildings will satisfy the collapse prevention and immediate occupancy performance level are calculated. All of the post Northridge buildings exhibit a high confidence of performing well in future earthquakes.